2017
DOI: 10.1111/wrr.12503
|View full text |Cite
|
Sign up to set email alerts
|

A comparative outcomes analysis evaluating clinical effectiveness in two different human placental membrane products for wound management

Abstract: Advances in tissue preservation have led to the commercialization of human placental membranes for the purposes of wound management with each product being characterized by different compositions and properties. The a priori specification of the research question in this investigator‐initiated study focused on the clinical outcomes in two nonrandomized, however statistically equal and homogenous patient cohorts receiving either a viable intact cryopreserved human placental membrane (vCPM) or a dehydrated human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Clinical outcomes of vCPM have been reported in multiple studies for wounds of various etiologies and locations. [12][13][14][15][16][17][18][19][20] In the present study using vLPM adjunct to SOC, we demonstrated similar closure rates to those rates previously shown in clinical studies with the cryopreserved formulation (Fig. 2).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Clinical outcomes of vCPM have been reported in multiple studies for wounds of various etiologies and locations. [12][13][14][15][16][17][18][19][20] In the present study using vLPM adjunct to SOC, we demonstrated similar closure rates to those rates previously shown in clinical studies with the cryopreserved formulation (Fig. 2).…”
Section: Discussionsupporting
confidence: 87%
“…[8][9][10][11] High closure rates for difficult-to-treat wounds of different etiologies and locations have been demonstrated in multiple vCPM clinical studies. [12][13][14][15][16][17][18][19][20] Two prospective studies, one utilizing amnionderived vCPM and one utilizing chorion-derived vCPM, demonstrated a 62% and 59.3% closure rate for chronic diabetic foot ulcers (DFUs) and chronic complex DFUs, respectively. 12,14 Results of these DFU prospective clinical trials are mirrored by reported DFU closure rates in real-world patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, a novel comparative effectiveness research technique was used to perform a retrospective non-randomized investigation to compare clinical trial data from chronic wound patients treated with hCVAM or a dehydrated-hAM. 8,20 The results showed that wounds treated with hCVAM closed at a significantly higher rate (63%) than those treated with the dehydrated membrane (18.2%) over 12 weeks. 20 Additionally, in vitro studies showed that hCVAM released lower levels of profibrotic transforming growth factor- β 1 (TGFB1), as well as decreased levels of pro-inflammatory factors including interferon- γ (IFNG), chemokine (C–C motif) ligand 5 (CCL5), epidermal growth factor (EGF), and thrombopoietin, compared to devitalized hAM.…”
Section: Introductionmentioning
confidence: 97%
“…8,20 The results showed that wounds treated with hCVAM closed at a significantly higher rate (63%) than those treated with the dehydrated membrane (18.2%) over 12 weeks. 20 Additionally, in vitro studies showed that hCVAM released lower levels of profibrotic transforming growth factor- β 1 (TGFB1), as well as decreased levels of pro-inflammatory factors including interferon- γ (IFNG), chemokine (C–C motif) ligand 5 (CCL5), epidermal growth factor (EGF), and thrombopoietin, compared to devitalized hAM. 56 On the other hand, hAM-derived ECM itself has been shown to promote enhanced cell proliferation compared to intact hCVAM.…”
Section: Introductionmentioning
confidence: 97%